SARS-CoV-2 mutant spectra as variant of concern nurseries: endless variation? - Martínez-González, Brenda; Soria, María Eugenia; Mínguez, Pablo; Lorenzo-Redondo, Ramón; Salar-Vidal, Llanos; López-García, Alberto; Esteban-Muñoz, Mario; Durán-Pastor, Antoni; Somovilla, Pilar; García-Crespo, Carlos; de Ávila, Ana Isabel; Gómez, Jordi; et al. (Frontiers in Microbiology, 2024)
SARS-CoV-2 isolates of a given clade may contain low frequency genomes that encode amino acids or deletions which are typical of a different clade. Here we document that in 6 out of 11 SARS-CoV-2 isolates from COVID-19 patients, the mutant spectrum of the spike (S)-coding region included two or more amino acids or deletions, that correspond to discordant viral clades. A similar observation is reported for laboratory populations of SARS-CoV-2 USA-WA1/2020, following a cell culture infection in the presence of remdesivir, ribavirin or their combinations. Moreover, some of the cladediscordant genome residues are found in the same haplotype within an amplicon. We evaluate possible interpretations of these findings, and reviewed precedents for rapid selection of genomes with multiple mutations in RNA viruses. These considerations suggest that intra-host evolution may be sufficient to generate minority sequences which are closely related to sequences typical of other clades. The results provide a model for the origin of variants of concern during epidemic spread ─in particular Omicron lineages─ that does not require prolonged infection, involvement of immunocompromised individuals, or participation of intermediate, non-human hosts.